2021
DOI: 10.1126/sciadv.abf6709
|View full text |Cite
|
Sign up to set email alerts
|

Zona incerta subpopulations differentially encode and modulate anxiety

Abstract: Despite recent clinical observations linking the zona incerta (ZI) to anxiety, little is known about whether and how the ZI processes anxiety. Here, we subject mice to anxious experiences and observe an increase in ZI c-fos-labeled neurons and single-cell calcium activity as well as an efficient effect of ZI infusion of diazepam, a classical anxiolytic drug. We further identify that somatostatin (SOM)-, calretinin (CR)-, and vesicular glutamate transporter-2 (Vglut2)expressing cells display unique electrophysi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 61 publications
1
13
0
Order By: Relevance
“…Moreover, it has been suggested that activation of the mesocorticolimbic pathway, which originates in A10 DA neurons in the ventral tegmental area (VTA), is associated with the contextual fear conditioning (Bariselli et al, 2016). The A13 DA neuron group is located in the zona incerta (ZI), which has comprehensive outputs and inputs to almost the entire neuroaxis (Mitrofanis, 2005;Zhang and van den Pol, 2017;Zhou et al, 2018;Li et al, 2021). Moriya et al indicated that ZI DA neurons project to the periaqueductal gray and the central nucleus of the amygdala, two locations that contain key circuits in nociceptive processing, and nociceptive processing is known as an aversive stimulus (Moriya et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it has been suggested that activation of the mesocorticolimbic pathway, which originates in A10 DA neurons in the ventral tegmental area (VTA), is associated with the contextual fear conditioning (Bariselli et al, 2016). The A13 DA neuron group is located in the zona incerta (ZI), which has comprehensive outputs and inputs to almost the entire neuroaxis (Mitrofanis, 2005;Zhang and van den Pol, 2017;Zhou et al, 2018;Li et al, 2021). Moriya et al indicated that ZI DA neurons project to the periaqueductal gray and the central nucleus of the amygdala, two locations that contain key circuits in nociceptive processing, and nociceptive processing is known as an aversive stimulus (Moriya et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Kelly Tan's lab reported the involvement of SST-positive neurons in the ZI in the regulation of anxiety behavior [ 12 ]. They found that the SST-positive neurons in the ZI are activated when mice are in anxiety-inducing environment.…”
Section: Discussionmentioning
confidence: 99%
“…The zona incerta (ZI), originally described as a “zone of uncertainty” [ 1 ], consists of heterogeneous neuron subtypes and extensive efferent and afferent projections connected with various regions across the brain [ 2 ]. Recent studies have revealed the involvement of the ZI in various functions including binge-like eating [ 3 ], hunting [ 4 , 5 ], sleep [ 6 ], parkinsonian motor symptoms [ 7 ], fear learning and fear memory [ 8 – 11 ], anxiety [ 12 ], and novelty-seeking [ 13 ], as well as neuron development [ 14 ]. These behaviors are closely associated with physiological functions that are beneficial for the well-being and survival of animals [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…As an inhibitory subthalamic nucleus, zona incerta (ZI) integrates various sensory modalities and feeds them to a series of downstream areas, including the thalamus, hypothalamus, midbrain, and spinal cord, to modulate behavioral outputs and convey motivational states ( Mitrofanis, 2005 ; Wang et al, 2020b ). As yet, ZI has been demonstrated to regulate fear memory ( Zhou et al, 2018 ; Venkataraman et al, 2019 ), defensive behavior ( Chou et al, 2018 ; Wang et al, 2019 ), predatory hunting ( Zhao et al, 2019 ), anxiety ( Li et al, 2021 ), and sleep ( Liu et al, 2017 ). Interestingly, ZI is also implicated in pain modulation.…”
Section: Introductionmentioning
confidence: 99%